(untitled) (Research, Society and Development, 2020)
With the increase of greater rhea (Rhea Americana) as an animal of production (meat, leather, feathers, eggs and fat) the interest for research related to these animals, because other animals are still used (ostrich and emu) as source of foundation to meet the nutritional, physiological, behavioral and environmental demands that affect these animals. The aim of this work was to evaluate the behavior and effect of the environment under greater rhea, from 30 to 90 days of age, fed with balanced diet (conventional and alternative). Were evaluated the behaviors (walking for the enclosure, pecking, walking to and fro, foraging, lying, sleeping, looking for the light, eating ration, drinking water, eating fruit, coprophagy, stereotypy), related to the diet, to the schedules of observation, to the atmosphere and the corporal temperature in the experimental groups. The test used for the data behaviors was it of Kruskal Wallis to 5% of probability and for the environmental data, the one of Tukey to 5% of probability. There was (P < 0.05) for knee behaviors, lying down, ingestive behaviors, seeking light and pecking. Sleeping, walking and stereotyping behaviors were influenced by diet. None of the environmental parameters were significant in relation to diet.